Sensorized Foam Actuator with Intrinsic Proprioception and Tunable Stiffness Behavior for Soft Robots. (28th June 2021) - Murali Babu, Saravana Prashanth; Visentin, Francesco; Sadeghi, Ali; Mondini, Alessio; Meder, Fabian; Mazzolai, Barbara
Abstract : Soft Actuators In article number 2100022, Saravana Prashanth Murali Babu, Barbara Mazzolai, and co‐workers develop an easy‐to‐implement integrated soft actuator by incorporating conductive foam. The sensorized foam has intrinsic proprioception and can sense direct actuation and passive deformation due to external stresses through pore shape evolution. At the same time, the actuator has variable stiffness properties and is strong enough to lift 500 times its own weight with a load of 235 N. The proposed sensorized foam actuator (SFA) successfully demonstrates various soft robotics applications to validate the proprioceptive feedback and variable stiffness properties while maintaining softness.